Design, synthesis and evaluation of novel indandione derivatives as multifunctional agents with cholinesterase inhibition, anti-β-amyloid aggregation, antioxidant and neuroprotection properties against Alzheimer's disease. Issue 16 (15th August 2016) - Mishra, Chandra Bhushan; Manral, Apra; Kumari, Shikha; Saini, Vikas; Tiwari, Manisha
Graphical abstract: Highlights: Novel indandiones were designed and synthesized as multifunctional agents for AD. Most of the compounds have shown good AChE, BuChE and Aβ aggregation inhibitory activity. Compounds34 and38 appeared as most active derivative which possesses excellent AChE, BuChE and Aβ aggregation inhibition. Both compounds also displayed promising antioxidant activity and neuroprotection in SH-SY5Y cells. Abstract: A series of novel 2-(4-(4-substituted piperazin-1-yl)benzylidene)-1 H -indene-1, 3(2 H )-diones were designed, synthesized and appraised as multifunctional anti-Alzheimer agents. In vitro studies of compounds27 –38 showed that these compounds exhibit moderate to excellent AChE, BuChE and Aβ aggregation inhibitory activity. Notably, compounds34 and38 appeared as most active multifunctional agents in the entire series and exhibited excellent inhibition against AChE (IC50  = 0.048 μM:34 ; 0.036 μM:38 ), Aβ aggregation (max% inhibition 82.2%, IC50  = 9.2 μM:34 ; max% inhibition 80.9%, IC50  = 10.11 μM:38 ) and displayed significant antioxidant potential in ORAC-FL assay. Both compounds also successfully diminished H2 O2 induced oxidative stress in SH-SY5Y cells. Fascinatingly, compounds34 and38 showed admirable neuroprotective effects against H2 O2 and Aβ induced toxicity in SH-SY5Y cells. Additionally, both derivatives showed no considerable toxicity in neuronal cell viability assay and represented drug likeness properties in the primarily pharmacokinetics study. All these results together, propelled out that compounds34 and38 might serve as promising multi-functional lead candidates for treatment of AD in the future.